2017
DOI: 10.1089/rej.2016.1887
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Between Choroid Plexus Epithelial Cell-Conditioned Medium and Knockout Serum Replacement Converts Human Adipose-Derived Stem Cells to Dopamine-Secreting Neurons

Abstract: Human adipose-derived stem cells (hADSCs) have great capacity to differentiate into mesodermal origins as well as nonmesodermal lineages, including neural cells. This valuable feature paves the way for the therapeutic application of hADSCs for neurodegenerative maladies such as Parkinson's disease (PD). We tested the capacity of choroid plexus epithelial cell-conditioned medium (CPEC-CM) alone or cocktailed with knockout serum (KS) to induce dopaminergic (DAergic) differentiation of hADSCs. To this end, hADSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Our findings confirmed that implantation of HCMSCs‐derived DA neuron‐like cells into the striatum of a rat model of PD could noticeably impede morphological and behavioral alterations, following 6‐OHDA‐induced lesion. In addition, our two recent experiments displayed DA differentiation of adipose‐derived MSCs under conditioned‐medium treatment (Boroujeni, Gardaneh, Shahriari, Aliaghaei, & Hasani, ; Rad et al, ). Moreover, Bjorklund et al (Björklund et al, ) disclosed that ES cells could develop into functional DA neuron‐like cells, leading to decline in motor asymmetries, accompanied by normalized DA presynaptic markers in damaged animal brain, following cell transplant.…”
Section: Discussionmentioning
confidence: 78%
“…Our findings confirmed that implantation of HCMSCs‐derived DA neuron‐like cells into the striatum of a rat model of PD could noticeably impede morphological and behavioral alterations, following 6‐OHDA‐induced lesion. In addition, our two recent experiments displayed DA differentiation of adipose‐derived MSCs under conditioned‐medium treatment (Boroujeni, Gardaneh, Shahriari, Aliaghaei, & Hasani, ; Rad et al, ). Moreover, Bjorklund et al (Björklund et al, ) disclosed that ES cells could develop into functional DA neuron‐like cells, leading to decline in motor asymmetries, accompanied by normalized DA presynaptic markers in damaged animal brain, following cell transplant.…”
Section: Discussionmentioning
confidence: 78%
“…Cell transplantation is believed to be a promising therapeutic approach in the treatment process of neurodegenerative disorders such as PD when there are no definite pharmaceutical therapies . However, tumorigenesis and ethical issues must always be considered when it comes to cell transplantation …”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] The current study aimed to make a comparison between the differentiation capacity of the OE-MSCs and OB-NSCs into DA-ergic neuron-like cells under the inductive effect of the transforming growth factor β (TGF-β) differentiation factor, which is substantially needed to induce DA-ergic cells in the mesencephalon and indeed promotes the DA-ergic neurons' survival. 47…”
Section: Introductionmentioning
confidence: 99%
“…Han et al, 2014;Safford et al, 2002). In recent years, several studies have documented dopaminergic differentiation of hADSCs (Boroujeni, Gardaneh, Shahriari, Aliaghaei, & Hasani, 2017;Faghih, Javeri, Amini, & Taha, 2019;Marei et al, 2018;Singh et al, 2017;Soheilifar et al, 2018) which raises the hope of using these cells for the treatment of Parkinson's disease. In a recent work, we successfully induced differentiation of hADSCs to dopaminergic neurons by a growth factor-cocktail consisting of SHH, bFGF, FGF8 and BDNF.…”
Section: Introductionmentioning
confidence: 99%